Laparoscopic appendicectomy in higher grades of appendicitis - A R, Srigireesh; R, Natarajan; R, Karunanithi; V, Balakrishnan; M, Loganathan (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Introduction: Complicated appendicitis has higher morbidity and mortality than non-complicated appendicitis. Despite of many clinical studies and meta-analyses of the various studies it remains confusion for the surgeons to decide which approach, whether Open (OA) or Laparoscopic Appendicectomy (LA) is the most efficacious and effective for complicated appendicitis. This is because, earlier studies reported the occurrence of post-operative complication like intraabdominal abscess following LA. Objectives: Primary: 1) To evaluate the results of laparoscopic appendicectomy in various grades complicated appendicitis. (Grade III, IV, V). Secondary- 2) To find out the percentage of postoperative complications. 3) To compare the post-operative pain among three grades of complicated appendicitis. Methodology: Patients with clinical suspicion of complicated appendicitis underwent blood and imaging investigations and Alvarado’s scoring was done and patients with very probable appendicitis were subjected for laparoscopy and grading of appendicitis will be done and Grade III, IV, V patients will be included in our study and their peri-operative parameters will be analysed and compared among the three grades of appendicitis. Results: In 46 patients LA was performed. 4(8%) patients needed conversion. We had 47.83%, 32.61% and 19.57% of Grade III, IV V patients respectively. Mean operative time and hospital stay were 68.8 mins and 3.91 days respectively. We found that there is a statistically significant difference among three grades in post-op pain that was present on post-op day 1 (<0.01) and 2 (<0.05). Conclusion: There was no statistically significant difference on comparing the above variables among the three grades of appendicitis.